Kolacjonowanie przekazów wierszy Franciszka Dionizego Kniaźnina na podstawie wybranych liryków zawartych w autografie poety – dylematy edytorskie - Bednarek, Beata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
Franciszek Dionizy Kniaźnin has created manuscript for a few years. It was a kind of his poetica will. In this collection, titled Poezje Franciszka Dionizego Kniaźnina ręką własną pisane, author included works published in three previous collections volumes of verse as well as completely new poems. Reused works had many editorial alterations compared to original ones. First time published works had been totally unknown before. Poezje Franciszka Dionizego Kniaźnina ręką własną pisane was not published as printed, scientific edition yet. This article describes today’s editor dilemmas about making a critical edition of four first book contained in the first volume of autograph. Mainly it is focused on the problem of comparasion variants of particular texts, which often are very different.